The Effects of Profitability, Environmental Performance, and Company Size on Carbon Emission Disclosure among Companies in Indonesia - Gebi Evelin Lumbantungkup; Muhammad Dimar Alam (CV. Publikasi Indonesia, 2026)
Carbon emission disclosure (CED) has become increasingly important as Indonesia commits to achieving Net Zero Emissions by 2060. The basic materials sector, as the largest contributor to national emissions (40%), faces increasing pressure to enhance environmental transparency. However, CED practices in Indonesia remain voluntary, resulting in significant variations in disclosure levels among companies. This study aims to examine the effects of profitability, environmental performance, and firm size on carbon emission disclosure among basic materials sector companies listed on the Indonesia Stock Exchange. This quantitative study employs a sample of 126 observations obtained through purposive sampling from companies in the basic materials sector during the 2022–2024 period. The data were analyzed using panel data regression with EViews software. The findings indicate that higher profitability and strong environmental performance have not yet become primary determinants of carbon emission disclosure, whereas larger firms tend to experience greater stakeholder pressure and legitimacy demands, encouraging them to disclose carbon emissions more extensively and comprehensively. This study contributes to enriching the understanding of legitimacy theory and stakeholder theory and provides a reference for regulators in strengthening carbon emission disclosure policies through more stringent and standardized reporting frameworks.